Insoluble hyaluronan films obtained by heterogeneous crosslinking with iron(III) as resorbable implants - Mrázek, Jiří; Kohout, Jaroslav; Kmječ, Tomáš; Nešporová, Kristina; Chmelař, Josef; Kubala, Lukáš; Velebný, Vladimír (International journal of biological macromolecules, 2021)
We present water-insoluble hyaluronan films crosslinked by trivalent iron developed as potential resorbable implants. The films were crosslinked by sorption of ferric salt into solid HA films in water/2-propanol bath. These heterogeneously crosslinked films (het-FeHA) remained tough and dimensionally stable when rehydrated in saline. In contrast, films prepared by drying the well-known homogeneous ferric hyaluronate gels (hom-FeHA) softened upon rehydration and expanded rapidly. Differences between hom-FeHA and het-FeHA result from polymer network topology (dominant inter- or intra-molecular crosslink, respectively). Moreover, Mössbauer spectroscopy of het-FeHA revealed diiron complexes, while iron in the hom-FeHA was present exclusively as γ-FeOOH nanoparticles or amorphous FeOOH. The biocompatibility tests of het-FeHA did not show any adverse effect and the sample disintegrated within one day when implanted in mice peritoneum. In conclusion, we developed implantable hyaluronan-based free-standing film with minimal swelling that can be resorbed quickly enough to avoid induction of foreign-body reaction.
Keywords: Animals; peritoneum; 3T3 Cells; Peritoneum; vstřebatelné implantáty; železo; Ferric hyaluronate; Nanoparticles; Mössbauer spectroscopy; Hydrogels; Mice; kyselina hyaluronová; Hyaluronan film; Cross-Linking Reagents; nanočástice; myši; Absorbable Implants; Hyaluronic Acid; reagencia zkříženě vázaná; Male; Iron; buňky 3T3; hydrogely; Resorbable implant; zvířata; mužské pohlaví; Mice, Inbred C57BL; Ionic crosslink; myši inbrední C57BL